Andreas Vesalius: novel anatomist of the Roman empire: a review article - Deka, Debajani; Talukdar, Hrishikesh (International Journal of Research in Medical Sciences, 2026)
Andreas Vesalius, born in Brussels on December 31, 1514, and passing away in Zante in 1564, hailed from a distinguished line of physicians. He grew up in the coastal low countries, which were part of the seventeen provinces. These regions, now encompassing mainly The Netherlands, Belgium, Luxembourg, and the north of France, enjoyed a certain degree of cultural, economic, and political autonomy. In 1529, Vesalius left Brussels to pursue studies at the Catholic University of Leuven. from 1533 to 1536, he journeyed to France to further his medical education at the University of Paris. Vesalius' predecessors and contemporaries had also written about anatomical teaching, his work "De Humani Corporis Fabrica" is now widely regarded as a pivotal advancement in the methodology and teaching of anatomical science. Vesalius' predecessors and contemporaries had also written about anatomical teaching, his work "De Humani Corporis Fabrica" is now widely regarded as a pivotal advancement in the methodology and teaching of anatomical science.